2018
DOI: 10.1152/ajprenal.00485.2017
|View full text |Cite
|
Sign up to set email alerts
|

With no lysine kinase 4 modulates sodium potassium 2 chloride cotransporter activity in vivo

Abstract: With no lysine kinase 4 (WNK4) is essential to activate the thiazide-sensitive NaCl cotransporter (NCC) along the distal convoluted tubule, an effect central to the phenotype of familial hyperkalemic hypertension. Although effects on potassium and sodium channels along the connecting and collecting tubules have also been documented, WNK4 is typically believed to have little role in modulating sodium chloride reabsorption along the thick ascending limb of the loop of Henle. Yet wnk4 mice (knockout mice lacking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 46 publications
4
33
0
Order By: Relevance
“…Here, we investigate the role of WNK4 in calcium transport along the TAL and DCT using WNK4 −/− animals. While baseline urinary calcium levels are known to be normal in WNK4 −/− animals (Castaneda‐Bueno et al ; Terker et al ), we have reported differences in urine calcium excretion between controls and knockout animals in response to dietary stress (Terker et al ). We sought to determine the role of WNK4 in calcium handling under conditions known to perturb calcium homeostasis.…”
Section: Introductionmentioning
confidence: 59%
See 3 more Smart Citations
“…Here, we investigate the role of WNK4 in calcium transport along the TAL and DCT using WNK4 −/− animals. While baseline urinary calcium levels are known to be normal in WNK4 −/− animals (Castaneda‐Bueno et al ; Terker et al ), we have reported differences in urine calcium excretion between controls and knockout animals in response to dietary stress (Terker et al ). We sought to determine the role of WNK4 in calcium handling under conditions known to perturb calcium homeostasis.…”
Section: Introductionmentioning
confidence: 59%
“…The loop diuretic furosemide causes hypercalciuria, both chronically and acutely. We reported decreased furosemide‐induced natriuresis in WNK4 −/− mice (Terker et al ). To determine effects of WNK4 deletion on furosemide‐induced calcium excretion, we quantified urine calcium following acute furosemide treatment.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…The with-no-lysine (WNK) kinases (WNK1, WNK3, and WNK4) are the first step in an enzymatic cascade which increases activity of the Na + /K + /2Cl − and Na + /Cl − co-transporters [ 40 43 ]. Chloride binds to the catalytic site of the kinases, thus inactivating them [ 44 , 45 ].…”
Section: Chloride and Outcomementioning
confidence: 99%